2021
DOI: 10.1029/2021gl095138
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Electron Acceleration Process in Solar Flare: A Case Study

Abstract: Solar flares are a major particle accelerator in the solar system (Reames, 2015). In the standard flare model (aka CSHKP model) (Carmichael, 1964;Hirayama, 1974;Kopp & Pneuman, 1976;Sturrock, 1966), magnetic reconnection at the reconnection current sheet powers the particle acceleration process. Recent RHESSI imaging observations (Liu et al., 2013) have revealed that energetic electrons may be accelerated at reconnection exhausts. It is possible that energetic electrons propagating downward and upward undergo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(34 citation statements)
references
References 42 publications
7
27
0
Order By: Relevance
“…In this article, we perform a statistical study of the release time for 29 impulsive SEE events from 2002 to 2016 using in situ electron data from WIND/3DP and HXR observation from RHESSI and Fermi/GBM. Based on the recently developed FVDA (Zhao et al, 2019), we examined the release time of both the outward-and downward-propagating near-relativistic electrons and showed that for all events, there is a distinct time delay, mainly distributed between 0 and 1,000 s, which is consistent with the case study of G. and G. Li et al (2021). The release time of in situ electrons also shows clear energy dependence with higher energy electrons released later, consistent with a time-dependent acceleration process.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In this article, we perform a statistical study of the release time for 29 impulsive SEE events from 2002 to 2016 using in situ electron data from WIND/3DP and HXR observation from RHESSI and Fermi/GBM. Based on the recently developed FVDA (Zhao et al, 2019), we examined the release time of both the outward-and downward-propagating near-relativistic electrons and showed that for all events, there is a distinct time delay, mainly distributed between 0 and 1,000 s, which is consistent with the case study of G. and G. Li et al (2021). The release time of in situ electrons also shows clear energy dependence with higher energy electrons released later, consistent with a time-dependent acceleration process.…”
Section: Discussionsupporting
confidence: 82%
“…In a recent paper, W. Wang et al (2021) examined the spectral relationship between HXR-producing electrons and SEEs and also concluded that the HXR-producing electrons and SEE electrons are of two different populations. They also suggested that two (or more) reconnection processes may occur at the reconnection site, and the HXR-generating electrons are electrons that experience two consecutive accelerations, that is, they are downward-traveling electrons produced at the first reconnection site which occur high in the corona.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations